2022
DOI: 10.3390/vaccines10020207
|View full text |Cite
|
Sign up to set email alerts
|

Protective Efficacy of Novel Oral Biofilm Vaccines against Photobacterium damselae subsp. damselae Infection in Giant Grouper, Epinephelus lanceolatus

Abstract: Photobacterium damselae subsp. damselae is a pathogen that mainly infects a variety of fish species. There are many antibiotic-resistant strains of Photobacterium damselae subsp. damselae. In a previously published article, we described the production method for a novel oral biofilm vaccine. In the study reported herein, we confirmed the protective effect of the oral biofilm vaccine against Photobacterium damselae subsp. damselae. Twenty-eight days after vaccination, phagocytosis increased by 256% relative to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 47 publications
1
1
0
Order By: Relevance
“…A higher protection level (85.4%) was achieved through the oral vaccine against V. anguillarum biofilm was compared to the free cell vaccine (27%) in Asian seabass, Lates calcarifer [ 29 ]. Findings of the present study closely agree with the similar study conducted in Taiwan [ 56 , 57 ]. They had reported significantly higher RPS in biofilm vaccines against Lactococcus garvieae infection in Mullet (77%) and in Photobacterium damselae infection in giant grouper (62%).…”
Section: Discussionsupporting
confidence: 93%
“…A higher protection level (85.4%) was achieved through the oral vaccine against V. anguillarum biofilm was compared to the free cell vaccine (27%) in Asian seabass, Lates calcarifer [ 29 ]. Findings of the present study closely agree with the similar study conducted in Taiwan [ 56 , 57 ]. They had reported significantly higher RPS in biofilm vaccines against Lactococcus garvieae infection in Mullet (77%) and in Photobacterium damselae infection in giant grouper (62%).…”
Section: Discussionsupporting
confidence: 93%
“…A recent study demonstrated protection against Photobacterium damselae subsp. damselae in giant grouper (Epinephelus lanceolatus); this platform used a formalin-inactivated biofilm that was incorporated directly into the feed, which provided an RPS of 62% relative to the whole-cell formalin-inactivated vaccine [141]. This same biofilm vaccination method has also demonstrated protection against L. garvieae in mullet (Mugil cephalus) [142].…”
Section: History and Present Status Of Oral Vaccinationmentioning
confidence: 99%